ASUHAN KEBIDANAN PADA IBU K DENGAN HUBUNGAN STATUS GIZI PADA IBU NIFAS DENGAN PEMULIHAN LUKA PERENIUM DI TPMB DEWI SANDRA LUBIS KECAMATAN MEUREBO KABUPATEN ACEH BARAT TAHUN 2025 - Husnita, Rika; Asmanidar, Asmanidar; Julianti, Rina; Zahara, Evi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Introduction: The postpartum period or breastfeeding period is a very important period, this is because after giving birth the mother will need time to recover her condition and prepare breast milk as a staple food for her baby. The postpartum period is the period during labor and immediately after birth which includes the following weeks when the reproductive tract returns to its normal non-pregnant state. Nutritional needs during the postpartum and breastfeeding period increase by 25%, namely for breast milk production and meeting fluid needs which increase three times than usual. Additional calories for breastfeeding mothers is 500 kcal per day. Long perineal wound healing in vaginal delivery women can lead to infection. One of the factors that were correlated to wound healing is a nutritional factors.Objective:research provides postpartum care to mother K so that she knows the balanced nutrition needed by postpartum women for recovery Research method: This care design is in the form of a case study with a qualitative approach, the subject of this case study is mother K, 23 years old G2P1A0, at 2 days postpartum with the relationship between nutritional recovery of postpartum mothers and selection of perennial wounds in Aceh district West, this research was carried out on March 12 2025. Results: The results of the research showed that after being given care, most of the respondents had their nutritional needs met and their perineal wounds experienced recovery from perineal wounds. Conclusions The majority of postpartum mothers in BPM Dewi Sandra Lubis, Meurebo subdistrict, have their nutritional needs met.Suggestion: Future research is expected to be able to analyze the nutritional factors that are most dominant in the recovery of perineal wounds. Increasing nutritional knowledge for postpartum mothers also needs to be done to avoid a culture of abstinence from eating. development of complementary midwifery orphanages in accordance with the vision and mission of the midwifery study program.